1H NMR-based metabolic study reveals the improvements of bitter melon (Momordica charantia) on energy metabolism in diet-induced obese mouse. (1st December 2016) - Bian, Hui-Xi; Wu, Ze-Yu; Bao, Bin; Cai, Jing; Wang, Xin; Jiang, Ying; Liu, Jian; Qu, Wei
Abstract: Context: Obesity can be ameliorated by some natural products such as polyphenol, flavones and saponin. As a typical medicinal plant, Momordica charantia L. (Cucurbitaceae) (bitter melon, BM) contains these natural chemicals and reduces diet-induced obesity in mice. Objective: This study evaluates the metabolic effects of dietary BM supplement, investigates a global metabolic profile and determines associated perturbations in metabolic pathways. Materials and methods: Male C57BL/6 mice were fed with low-fat diet (LFD), high-fat diet (HFD) and HFD supplemented with 5% BM based on 37.6 g/kg body weight in average for 12 weeks, respectively. Then energy metabolism was quantified using PhenoMaster/LabMaster. The spectroscopy of urine was acquired by nuclear magnetic resonance and latent biomarkers were identified. Pattern recognition analysis was used to discriminate associated metabolic profiles. Results: Dietary BM supplement reduced body weight gain (−0.15-fold, p  < 0.01) and blood glucose levels (−0.19-fold, p  < 0.01) in HFD-fed mice. Meanwhile, the levels of energy metabolism were enhanced (0.08–0.11-fold, p  < 0.01). According to pattern recognition analysis, dietary BM supplement changed metabolic profiles in HFD-fed mice and the modified profiles were similar to those in LFD-fed mice. Finally, the mapping of metabolic pathways showed that dietary BM supplement primarily affected glucose metabolism-associated pathways. Discussion and conclusion: The results indicated that BM improves weight loss in diet-induced obesity and elevate energy expenditure in HFD-fed mice. The pattern recognition with metabolic study may be used as a noninvasive detection method to assess the effects of dietary BM supplement on mouse energy metabolism.